2021
DOI: 10.5267/j.ijdns.2021.6.003
|View full text |Cite
|
Sign up to set email alerts
|

Empirical study of Indonesian SMEs sales performance in digital era: The role of quality service and digital marketing

Abstract: This research aims to analyze the relationship between digital marketing on quality service, digital marketing on sales performance, quality service on sales performance, and digital marketing on Sales performance through quality service. The research methodology is a quantitative method and divided into research design and research subjects, data collection methods, and analysis methods. The study is conducted on 125 small and medium (SMEs) in Banten, Indonesia in the digital region. The study uses primary da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
40
0
8

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(49 citation statements)
references
References 1 publication
1
40
0
8
Order By: Relevance
“…They also need to deliver the products quickly. This study has confirmed the previous researches conducted by Guci, D. A., Ghazali, P. L., Foziah, N. H. M., and Arifin [21], T. Nuseir, M., Basheer, M. F., and Aljumah [22], and Djakasaputra, A., Wijaya, O., Utama, A., Yohana, C., Romadhoni, B., and Fahlevi [23]. DM also affects CA positively.…”
Section: ) Structural Model Testing (Inner Model)supporting
confidence: 91%
See 1 more Smart Citation
“…They also need to deliver the products quickly. This study has confirmed the previous researches conducted by Guci, D. A., Ghazali, P. L., Foziah, N. H. M., and Arifin [21], T. Nuseir, M., Basheer, M. F., and Aljumah [22], and Djakasaputra, A., Wijaya, O., Utama, A., Yohana, C., Romadhoni, B., and Fahlevi [23]. DM also affects CA positively.…”
Section: ) Structural Model Testing (Inner Model)supporting
confidence: 91%
“…DM has a positive effect on CA Valdez Palazuelos, O., and Sánchez Beltrán [18] , Gakiria [19] and Obeidat, U., Obeidat, B., Alrowwad, A., Alshurideh, M., Masadeh, R., and Abuhashesh [20] . DM has a positive effect on MP Guci, D. A., Ghazali, P. L., Foziah, N. H. M., and Arifin [21], T. Nuseir, M., Basheer, M. F., and Aljumah [22] and Djakasaputra, A., Wijaya, O., Utama, A., Yohana, C., Romadhoni, B., and Fahlevi [23]. Inn has a positive effect on CA Distanont, A., and Khongmalai [5], Olazo [24], Puspita, L. E., Christiananta, B., and Ellitan, [25], Udriyah, U., Tham, J., and Azam [26].…”
Section: Literature Reviewmentioning
confidence: 99%
“…In addition to AVE values, we could check 'Construct Reliability'(CR) to double-check an internal consistency even if we already checked the 'Cronbach alpha' value (See Table 6). However, prior studies suggested that CR is a less biased estimate of reliability than 'Cronbach alpha' and the acceptable value of CR is 0.7 and above [59,60]. As seen in Table 9, all main factors' CR values were greater than 0.7, thus, we could double-check a high degree of reliability for the constructs.…”
Section: Confirmatory Factor Analysismentioning
confidence: 89%
“…Weaknesses in the marketing management aspects of Micro, Small and Medium Enterprises are caused by [16]: a. Micro, Small and Medium Enterprises only market their products to one market. b. Micro, Small and Medium Enterprises make it easier to sell their products on credit.…”
Section: Finding and Discussionmentioning
confidence: 99%